Edukasi Pemanfaatan Daun Tembelekan sebagai Antiseptik Luka Bakar di RT 09 Kelurahan Lambara Kecamatan Tawaeli Sulawesi Tengah: Education on the Use of Tembelekan Leaves as an Antiseptic for Burns in RT 09, Lambara Village, Tawaeli District, Central Sulawesi - Magfirah, Magfirah; Dewi, Niluh Puspita; Halik, Nur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
First aid is the initial treatment for handling burns with the use of natural ingredients that are fast and precise and can improve the healing process, prevent the severity of injuries, reduce pain, and save lives. This community service activity aims to increase public knowledge about the use of tembelekan leaves as first aid for burns. The community service method is carried out by providing socialization in the form of counseling which is followed by a discussion session, questions and answers, and distributing questionnaires to measure community satisfaction with the service. Community service was carried out on November 30, 2024, with the target of the activity being the community in the Lambara Village Area, especially RT 09. The results of community satisfaction with the service carried out were community satisfaction with the method of delivering PKM material, the PKM program was by community needs, the PKM program improved thinking skills, the PKM program could be applied by the community and the community was willing to participate/get involved again, the average result was very satisfied, namely 90.83%, It can be concluded that this PKM activity is very beneficial for the Lambara Village community, especially RT 09.